The Implementation of Positive Behavioral Support in an Elementary School: Processes, Procedures, and Outcomes - Menendez, Anthony L.; Payne, Linda Donica; Mayton, Michel R. (Alberta Journal of Educational Research, 2008)
This article presents the processes and outcomes of a year of School-Wide Positive Behavior Support in a North Texas elementary school serving kindergarten through grade 3 students. Included is a description of a school treatment package that incorporated components such as facilitation of the teaming process, a lottery-type system of intermittent reinforcement, mystery motivators, and recognition assemblies, all targeted at increased student compliance with school rules. Positive outcomes included: (a) a reduction in the number of office referrals; (b) reduced frequency of rules-based violations on the part of students; (c) reduced use of punitive consequences such as time-outs, written reprimands, and student conferences on the part of the faculty and administration; and (d) an increase in scores on a state-mandated academic achievement assessment administered to grade 3 students.